PROFESSIONAL COUNSELOR PROFILE (Between Expectation and Reality) - A.R. Koesdyantho (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
To find out, to figure out, and to build image about professional counselors nowadays are like to find out an unidentified needle in the straw. The counselors may receive the approved of regulation No. 20, 2002 about National System of Education with joy, which explained that the counselors had been stated clearly and precisely in that regulation, and that it is equal at the same level with other professions in education field such as classroom teachers, course teachers, practice teachers, or others. Based on this fact, can counselors proud of their title without any attempts to change the paradigm so that the professional counselors deserve that title. The title of professional counselor is not automatically attached to someone without approval from an authorized firm or professional organization from which the institution that has authority to produce professional counselors are determined. Credentialing is one way to make profession parallelism and standardization for a counselor which includes certification, license, and accreditation. Keywords: counselors, professional, credentialing